Exercise Intensity Guidelines for Cancer Survivors: a Comparison with Reference Values - Gil-Rey, E.; Quevedo-Jerez, K.; Maldonado-Martin, S.; Herrero-Román, F. (International Journal of Sports Medicine, 2014)
The optimal dose of physical activity (PA) in cancer survivors (CS) is unknown due to the large variety of types of cancer, illness stages and treatments, low cardiorespiratory fitness, and physical inactivity. It is recommended that CS follow current PA guidelines for healthy population. There are no specific exercise prescription guidelines for CS. To know the cardiorespiratory parameters of CS in order to create exercise prescription guidelines for this population, 152 inactive CS were recruited to perform a cardiopulmonary exercise test. Peak oxygen uptake (VO2peak), ventilatory threshold (VT) and respiratory compensation point (RCP) determined 3 exercise intensity zones to create exercise intensity classification guidelines for CS. VO2peak (18.7±4.6 mL·kg−1·min−1) and peak heart rate (HRpeak) (145.1±17.9 bpm) were lower than the estimated values (p<0.001). Moderate intensity zone for CS was different from the current PA guidelines for healthy population: 41–64% VO2max, 55–70% HRmax, 23–48% HRres, 2.5–4 METs and 8–14 points on RPE scale. Intensities in PA guidelines for healthy population are not adapted to the characteristics of CS. For individual exercise prescription in CS specific PA guidelines should be used in order to maximize the benefits obtained by the use of aerobic exercise training.
Keywords: exercise prescription; survivorship; physical activity; quality of life